The Flexural Strength of Laminated Bamboo Composite Beam - Agus Priyanto, Iskandar Yasin, Dewi Sulistyorini (RENOVASI : Rekayasa Dan Inovasi Teknik Sipil, 2019)
For dry conditions the petung bamboo oven has an average tensile strength of 1900 kg/cm2 without books and 1160 kg/cm2 with books. Average compressive strength of petung bamboo is 2769 kg/cm2 for the base, 4089 kg/cm2 for the middle and 5479 kg/cm2 for the end. If wood and bamboo species are used as composite beams, it is expected to be able to save on the use of high quality wood and lower costs. Glulam beam specimens were made as many as 12 pieces. The variation of cross section of glulam beams is based on the number of dimensions of thickness of bamboo lamina against glulam beams. For pure sengon sliding blocks the highest percentage of wood damage in the amount of adhesive is 50/MDGL. The more the amount of adhesive is anchored, the higher the adhesive strength of the glulam beams. The highest average strength was achieved in the ratio of bamboo to beams by 25 percent, and the lowest in the ratio of bamboo to beams by 75 percent. But in general the increase in the strength of the glulam beams is influenced by an increase in the ratio of bamboo to glulam beams. For beams with a ratio of 50 percent bamboo and 75 percent, sengon wood collapses first. Glulam beam stiffness factor has increased, where the highest stiffness factor is achieved in the ratio of bamboo to glulam beams by 50 percent and the lowest in the ratio of bamboo to glulam beams by 0 percent